Analisis Potensi Sektor Ekonomi Di Kota Solo dan Semarang Provinsi Jawa Tengah dan Kota Yogyakarta Provinsi Daerah Istimewa Yogyakarta - Samosir, Hillary Irene; Primandhana, Wiwin Priana; Wahed, Mohammad (Ridwan Institute, 2021)
The cities which predicted to be the golden triangle are Yogyakarta, Solo, and Semarang. The three cities work together within the scope of DIY - Central Java. The analysis techniques applied and used in this research are Location Quotient, Shift Share and Klassen Typology. This research is conducted to know the superior sectors that may have an impact both internally and externally. The results of this research are that in these three cities or the golden triangle in Joglosemar, eight sectors based on Location Quotient analysis which are the processing industry sector, electricity and gas supply, water supply, waste handling, waste, and recycling; providing facilities as well as food; information and communication; financial and insurance services; housing; company services; government administration, defence and compulsory social security. Through the Shift Share analysis, these three cities have different sectors. For Yogyakarta, the growing and influential sector is the sector in providing facilities and food. However, in Semarang, there is a sector of electricity and gas supply; transportation and warehousing; housing; company services; education services; along with several other services that cannot be mentioned. In Solo itself, the growing and influencing sectors are the health services sector and social activities.